Strategi guru pendidikan agama Islam dalam menghadapi disrupsi digital diera revolusi industri 4.0 - Fadillah Julya Putri; Safira Laila Wulandari; Herlini Puspika Sari (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study aims to analyze the strategies employed by Islamic Religious Education (IRE) teachers in addressing digital disruption in the era of the Fourth Industrial Revolution. The study employs a qualitative approach using library research, drawing on scientific journals, books, and relevant documents from 2020 to 2025. Data collection was conducted through documentary analysis, while data analysis utilized content analysis, following the stages of reduction, presentation, and drawing conclusions. The results indicate that the primary strategies PAI teachers can implement include strengthening digital competencies, applying the TPACK model, utilizing blended learning, innovating digital learning media, and enhancing digital literacy grounded in Islamic values. Furthermore, collaboration among teachers, schools, and parents serves as a supporting factor in creating a conducive digital learning environment. The study’s conclusion emphasizes that digital disruption is not merely a challenge but also an opportunity to enhance the quality of Islamic Education (PAI) in an adaptive and innovative manner, while remaining grounded in Islamic values.